1984
DOI: 10.1111/j.1467-1770.1984.tb01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Feedback in Native‐nonnative Discourse

Abstract: This article reports the results of an investigation into how native speakers of English provide corrective feedback to errors in conversations with their normative speaker friends. We also present other types of noncorrective conversational repair. From approximately 12.7 hours of taped conversations in social settings, we learned that native speakers responded to errors by using either on‐record or off‐record corrective feedback. In addition, they used several noncorrective discourse devices to repair conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 14 publications
2
40
1
Order By: Relevance
“…when the NS in response to an NNS's error supplies corrective feedback with declaratory intonation and off-record corrective feedback; when the response can be either a question or a statement and can be interpreted in at least two ways: as corrective feedback or as continuing contributions to the conversation. Contrary to the investigation of Day et al (1984) only a few occurrences of on-record corrective feedback were found in this data base. One reason for this may be that self-repair is preferred before otherrepair in ordinary conversation (Schegloff et al, 1974).…”
Section: Lexical Miscommunicationcontrasting
confidence: 44%
“…when the NS in response to an NNS's error supplies corrective feedback with declaratory intonation and off-record corrective feedback; when the response can be either a question or a statement and can be interpreted in at least two ways: as corrective feedback or as continuing contributions to the conversation. Contrary to the investigation of Day et al (1984) only a few occurrences of on-record corrective feedback were found in this data base. One reason for this may be that self-repair is preferred before otherrepair in ordinary conversation (Schegloff et al, 1974).…”
Section: Lexical Miscommunicationcontrasting
confidence: 44%
“…This research indicated that teachers' attempts at error correction were frequently ambiguous and inconsistent and, therefore, that the value of correction was not clearly demonstrated. Other studies explored error correction by NSs in more naturalistic conversations (Chun, Day, Chenoweth, & Luppescu, 1982;Day, Chenoweth, Chun, & Luppescu, 1984), which revealed that NSs rarely correct learners' errors in conversation.…”
Section: The Role Of Negative Feedback and Positive Evidence In L2 Acmentioning
confidence: 99%
“…Asymmetries in language competence, as a special kind of knowledge asymmetry, obviously exist in many conversations between non-native and native adult speakers, where they can lead to explications, collaborative word-searches, and a variety of forms of corrective feedback (e.g., Chun, Day, Chenoweth, & Luppescu, 1982;Dausendscho Èn-Gay, Gu Èlich, & Krafft, 1995;Day, Chenoweth, Chun, & Luppescu, 1984). These activities have been classified as language-learning strategies and are employed by both native and non-native participants in an attempt to develop linguistic competence (e.g., Faerch & Kasper, 1984;Tarone, 1980; see also the contributions in Kasper & Kellerman, 1997).…”
mentioning
confidence: 99%